Study of the pulmonary functiontest in Hypertensive patients - ديوب هيلين; مالك حجازية; باسم معروف (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: Hypertension is considered one of the most common chronic Diseases with worldwide prevalence reaching 25% of human beings according to WHO, and is also considered responsible for multi-system complications and effects like heart, brain, eye, and kidney which rises the importance of studying its effect upon respiratory system. PFTs is one of the easy, fast and low-cost investigations to test respiratory function in this population. Aim of the study: To study the relationship between spirometry tests and both of controlled and uncontrolled hypertension and to assess the pattern of lung function impairment, its severity and relation with age and gender. Patients and methods: A comparative cross-sectional study of 81 nonsmoking adult patients attending outpatient cardiovascular clinic of Tishreen University Hospital in Latakia between May 2021 and May 2022. Patients with chronic pulmonary diseases, cardiovascular diseases, heart failure, smokers and pregnant were excluded. After full medical evaluation, patients were classified according to their blood pressure status into three groups. Then, they underwent spirometry tests with measurement of forced vital capacity (FVC), forced expiratory volume in first second (FEV1), FEV1/FVC ratio and Forced mid-Expiratory Flow (FEF 25-75%). Results: All comparison groups were similar in age and sex. There were significant statistical decreases in FVC, FVC%, FEV1, FEV1% and PEF in uncontrolled hypertension group compared to the two other groups, but no significant statistical differences in FEV1/FVC ratio among all groups. Restrictive lung disease was statistically more common in the uncontrolled hypertension group. Conclusion: hypertension is related to low spirometric parameters and hypertension management may have a role in the prevention of such injury.